Factors associated with the worsening of COVID-19 symptoms among cohorts in community- or home-isolation care in southern Thailand - Thanit Sila; Thanit Sila; Wisanuwee Suriyaamorn; Chanavee Toh; Songyos Rajborirug; Smonrapat Surasombatpattana; Paramee Thongsuksai; Paramee Thongsuksai; Chanon Kongkamol; Chanon Kongkamol; Sarunyou Chusri; Phoomjai Sornsenee; et al. (Frontiers Media S.A., 2024)
IntroductionThis study aimed to investigate factors associated with time-to-referral due to worsening symptoms in patients with laboratory-confirmed COVID-19 in southern Thailand. While underlying diseases have been evaluated to assess COVID-19 severity, the influence of vaccinations and treatments is also crucial.MethodsA cohort of 8,638 patients quarantined in home or community isolation with laboratory-confirmed COVID-19 was analyzed. Survival analysis and the Cox proportional hazard ratio were employed to assess factors influencing time-toreferral.ResultsAge ≥ 60 years, neurologic disorders, cardiovascular disease, and human immunodeficiency virus infection were identified as significant risk factors for severe COVID-19 referral. Patients who received full- or booster-dose vaccinations had a lower risk of experiencing severe symptoms compared to unvaccinated patients. Notably, individuals vaccinated during the Omicron-dominant period had a substantially lower time-to-referral than those unvaccinated during the Delta-dominant period. Moreover, patients vaccinated between 1 and 6 months prior to infection had a significantly lower risk of time-to-referral than the reference group.DiscussionThese findings demonstrate early intervention in high-risk COVID-19 patients and the importance of vaccination efficacy to reduce symptom severity. The study provides valuable insights for guiding future epidemic management strategies and optimising patient care during infectious disease outbreaks.